Detection of environmental nanoplastics via surface-enhanced Raman spectroscopy using high-density, ring-shaped nanogap arrays - Luo, Sihai; Zhang, Junjie; de Mello, John C. (Frontiers in Bioengineering and Biotechnology, 2023)
Micro-and nano-plastics (MNPs) are global contaminants of growing concern to the ecosystem and human health. In-the-field detection and identification of environmental MNPs (e-MNPs) is critical for monitoring the spread and effects of e-MNPs but is challenging due to the dearth of suitable analytical techniques, especially in the sub-micron size range. Here we show that thin gold films patterned with a dense, hexagonal array of ring-shaped nanogaps (RSNs) can be used as active substrates for the sensitive detection of MNPs by surface-enhanced Raman spectroscopy (SERS), requiring only small sample volumes and no significant sample preparation. By drop-casting 0.2-μL aqueous test samples onto the SERS substrates, 50-nm polystyrene (PS) nanoparticles could be determined via Raman spectroscopy at concentrations down to 1 μg/mL. The substrates were successfully applied to the detection and identification of ~100-nm polypropylene e-MNPs in filtered drinking water and ~100-nm polyethylene terephthalate (PET) e-MNPs in filtered wash-water from a freshly cleaned PET infant feeding bottle.